Cardiac Resynchronization Therapy (CRT) Optimization: A Way Out for Non-Responders - A Case Report - Nabila Edhiningtyas Damaiati; Dony Yugo Hermanto (Jurnal Kardiologi Indonesia, 2026)
Background Non-responders account for 30% of patients receiving Cardiac Resynchronization Therapy (CRT). Optimization of CRT using Electrocardiographic (ECG) and Transthoracic Echocardiographic (TTE) guidance has been proposed as a strategy to enhance therapeutic efficacy in this subset. This case report presents a young female patient with advanced heart failure secondary to ischemic cardiomyopathy, highlighting the role of ECG- and TTE-guided CRT optimization in improving clinical and hemodynamic outcomes. Case Illustration A 37-year-old female presented with advanced heart failure. Her medical history was notable for recurrent episodes of acute coronary syndrome, multiple Percutaneous Coronary Interventions (PCIs), and Cardiac Resynchronization Therapy with Pacemaker (CRT-P) implantation, despite adherence to Guideline-Directed Medical Therapy (GDMT). On admission, the ECG demonstrated atrial sensing with consistent biventricular pacing. Laboratory evaluation revealed an elevated N-terminal pro–B-type natriuretic peptide (NT-proBNP) level of 5.462 pg/mL. TTE showed a severely reduced Left Ventricular Ejection Fraction (LVEF) of 20% and an absent A wave on mitral inflow Doppler, indicating impaired diastolic filling. Additionally, the Left Ventricular Outflow Tract (LVOT) Velocity Time Integral (VTI) was reduced to 7.4 cm, consistent with low forward stroke volume.Six months after the implantation, CRT optimization was performed using ECG and TTE guidance. Optimization resulted in a reduction of QRS duration to 129 ms, distinct separation of the mitral inflow E and A waves, an increase in LVOT VTI to 10.9 cm, and an improvement in functional capacity to New York Heart Association (NYHA) class III. Conclusion CRT optimization, guided by ECG or TTE, is critical in managing non-responders. In this case, it led to improved QRS duration, hemodynamics, and NYHA functional class. Routine reassessment should be considered in patients with persistent symptoms despite optimal GDMT to enhance clinical response.